2014
DOI: 10.1007/s12639-014-0437-3
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and molecular identification of Paradactylogyrus catlaius (Thapar 1948) in Catla catla (Hamilton 1822)

Abstract: Paradactylogyrus are small monogenean ectoparasites found mostly on the gills of Cyprinidae and are highly host specific. Conventionally these parasites are identified by microscopic analysis. In contrast to this conventional method, molecular identification using nuclear ribosomal DNA (rDNA) provides specific, sensitive and safe detection of parasites. The present study is aimed to identify the Paradactylogyrus on Catla catla using morphological and molecular tools. Morphologically the parasite is having hamu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In this regard, the aforesaid model approaches do not go through with morphological analysis. The studies performed on 28S rDNA sequences confirmed that there is a high specific similarity (Shrivastava 2013, Tamura et al 2013, Rana and Das 2016, Ahmadi et al 2017. The conventional bootstrap methods (NJ, ML and ME) were used for analysis of phylogeny.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this regard, the aforesaid model approaches do not go through with morphological analysis. The studies performed on 28S rDNA sequences confirmed that there is a high specific similarity (Shrivastava 2013, Tamura et al 2013, Rana and Das 2016, Ahmadi et al 2017. The conventional bootstrap methods (NJ, ML and ME) were used for analysis of phylogeny.…”
Section: Discussionmentioning
confidence: 85%
“…Due to the small morphological differences in the size and shape of the attachment apparatus among the species of Dactylogyrus, it does not give enough information to taxonomists as compared to 28S rDNA region. This can be attributed to the natural evolving of the gene or to the fact that this genus is organized in groups with a developed taxonomic level other than previously recognised (Rana andDas 2016, Ahmadi et al 2017). Molecular phylogenetic approaches have advantages over the morphological taxonomy.…”
Section: Discussionmentioning
confidence: 98%
“…The parasites attach to host gill by special attachment organs called opisthaptor which is positioned posteriorly on their body (Park, 2007). P. catlaius causing disease in catla has also been identified by 28S rDNA sequencing (Rana and Das, 2014). They feed on the blood and mucus of the host, which can place significant stress on the fish's body and can cause secondary infections (Rana, 2015).…”
Section: Introductionmentioning
confidence: 99%